Determination of Melatonin Differences between Day and Night Milk in Dairy Cattle - Özcan Şahin; Fikret Akyürek; İbrahim Aytekin; Saim Boztepe; İsmail Keskin (Journal of Agricultural Sciences)
The aim of this study was to determine the difference between melatonin hormone in night milk and melatonin concentration in day milk of Holstein cows. In this study, daytime milk obtained from 40 heads Holstein cows in the first lactation raised in a private dairy cattle farm in Karapınar district of Konya state province in Turkey and night milk samples taken from the same cows that were kept in darkness for one week were used. The milk samples were collected from day and night milking in order to determine the melatonin concentration with the help of Bovine Melatonin (MLT) Elisa Kit. In this study, melatonin concentration in day time and night time milk were determined as respectively 103.70 ± 6.61 pg mL-1 and 163.13 ± 8.96 pg mL-1. The difference between melatonin levels of day and night milk was statistically significant (P<0.01). Since significant difference occurred between melatonin concentration between day and night milk at the end of the study, it can be stated that night milk can be used for medical purposes that is used cure of some illnesses and producers can be provided with a new production source.